Peran Komunikasi dan Kepuasan Pernikahan Terhadap Coparenting pada Orangtua yang Memiliki Anak Usia Remaja - Asia, Tracey Sheilla; Setiawan, Jenny Lukito Setiawan Lukito (Universitas Ciputra Surabaya, 2020)
This study aims to see the role of communication and marital satisfaction towards coparenting in parent who have adolescence. There are 3 hypothesis presented in this result of this study to see role of communication and marital satisfaction towards coparenting in parent who have adolescence. The result of study is that communication and marital satisfaction contributed significantly towards coparenting in parent who have adolescence. This study was conducted on 79 parents who have adolescence in Church X Samarinda. This study use quantitative method with correlational design. The result of multiple regression test showed that communication and marital satisfaction contributed significantly to coparenting (F= 36,522 : p <0.05). The result of multiple regression also showed that commuication contributed higher than marital satisfaction, and that is 38,9%(????2 = 0,389 ???? < 0,05). While marital satisfaction contributed 10,1%(????2 = 0,101 ???? < 0,05).